Physiological and Biochemical Properties of Sweet Potato as affected by Agronomic Practices Under Sub-Tropical North Eastern Hills of India - Sahoo, Manas Ranjan; Roy, Subhra Saikat; Singh, N Rakesh; Devi, Y Indrani; Prakash, Narendra; Ngachan, S V (JOURNAL OF ROOT CROPS, 2015)
The effect of spacing and nutrient management on physiological and biochemical properties of orangefleshed sweet potato var. Gouri was studied under foot hill conditions of Manipur. The physiological parameters such as relative water content (RWC) and chlorophyll stability index (CSI); biochemical parameters such as protein content, total soluble sugar (TSS) and reducing sugar (RS) and NPK contents in leaves and tubers showed significant variation due to spacings (S1: 60 x 20 cm and S2: 60 x 30 cm) and NPK rates (F1: 60:40:60 ; F2: 75:50:75; F3: 90:60:90 kg ha-1). The RWC and CSI increased with increasing nutrient doses under spacing S1 and decreased at spacing S2. The NPK content, TSS and RS in leaf tissues increased significantly with increasing doses of NPK. The leaf protein content increased with increasing rates of NPK at wider spacing (S2). The treatment combinations, S1F2 (33.0 t ha-1) and S2F3 (32.7 t ha-1) produced significantly higher tuber yield. The study revealed that NPK @ 75:50:75 kg ha-1 and spacing of 60 x 20 cm can be recommended for higher productivity and tuber quality of sweet potato under foot hill conditions of Manipur.